Accelerated weathering parameters for some aromatic engineering thermoplastics. Part 2: Polycarbonate copolymers, polyarylate and ABS. (November 2020) - Pickett, James E.; Kuvshinnikova, Olga; Sung, Li-Piin; Ermi, Brett D.
Highlights: Weathering acceleration parameters were determined using the NIST SPHERE. Polycarbonate copolymers and resorcinol polyarylate (RPA) exhibited reciprocity while ABS did not. ABS had a higher activation energy (Ea ) for yellowing than other aromatic polymers while RPA had a small negative Ea . ABS and RPA had higher rates of photodegradation when the relative humidity was ≤ 10%. Abstract: Understanding the responses of materials to environmental variables is essential for performing meaningful accelerated weathering and service life prediction. Samples of polycarbonate- b -resorcinol polyarylate copolymer (RPA), poly(acrylonitrile- co -butadiene- co- styrene) (ABS), and two polycarbonate copolymers with silicone or aliphatic diacids were exposed in the NIST (National Institute of Standards and Technology) SPHERE (Simulated Photodegradation via High Energy Radiant Exposure) to determine the effects of ultraviolet intensity (UV irradiance), temperature, relative humidity (RH), and UV wavelength on yellowing and gloss loss and were compared to other aromatic polymers. All showed proportional response to irradiance (i.e., reciprocity) except ABS, which deviated notably at elevated temperatures. The activation energy for ABS yellowing was higher than other aromatic polymers (31 kJ mol −1 ± 2 kJ mol −1 ) while RPA had a slightly negative activation energy (-5 kJ mol −1 ± 3 kJ mol −1 ), reflecting differences in their photodegradation mechanisms. These two polymers also exhibited faster degradation when the RH was ≤ 10 % compared to ≥ 50 % RH. Wavelength effects varied among the polymers. The results indicate that predictive accelerated weathering should be performed with UV sources that accurately reproduce sunlight, at temperatures as close as possible to use conditions, and with RH > 10 %.